Evaluation of corrugated core configuration effects on low-velocity impact response in metallic sandwich panels - Zurnacı, Erman; Gökkaya, Hasan (Walter de Gruyter GmbH, 2024)
Abstract Sandwich panels are used as body components of vehicles in many sectors, such as defense, aircraft, and aviation, due to their advanced mechanical properties and lightness. This study aims to investigate the effect of core configurations on mechanical performance and deformation behavior of metallic sandwich panels under low-velocity impact loading. For this purpose, metallic sandwich panels having monolithic and sliced core configurations were first produced. Low-velocity impact tests were carried out using varying energy levels (20, 40, 60 J) to examine how the intensity of influence affects the deformation of the sandwich panel. The perforation and deformation behavior on the upper surface plates of sandwich panels were evaluated. Experimental results showed that the core design significantly affects the impact behavior of sandwich panel samples. The sliced core configuration produced approximately 10 % more maximum contact force and absorbed 14 % more impact energy at high-impact energy levels. Additionally, the sliced core configuration delayed core collapse of the core in deformation situations where complete perforation does not occur.
Keywords: 7. Clean energy